Comparison of preventive health service provision before and after reorganization of primary care in Turkey: a community-based study - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
Aim To investigate the changes in the provision of preventive health services in terms of woman and child health after reorganization of the primary health care services. Background The primary care system in Turkey has undergone fundamental changes as a part of Health Transformation Program during last decade. But there was no community-based study to evaluate these changes. Method This community-based and cross-sectional study was conducted in 2010, just before the reorganization of primary care services and in 2015, five year after the reforms. The 30x7 cluster sampling method was used in Zumrutevler quarter of Maltepe District. The socio-demographic characteristics of the participants, the presence of the physician who can be consulted for any health problem, the presence of smokers at home were questioned. The women aged 18 years or older and gave consent provided information about history of pregnancy and birth, the number of follow-ups during pregnancy, family planning method usage, cervical and breast cancer screening, breastfeeding duration, vaccinations, and prophylactic iron and vitamin D supplementation for their children. Findings After the reorganization of primary care, more people stated that they had physicians to whom they could consult for all kinds of health problems (27.8 versus 44.7%; P<0.001) and that physician was the primary care physician (30.2 versus 64.7%; P<0.001). The reported frequency of at least one smoker at home was decreased after reorganization of primary care (63.6 versus 53.1%; P=0.034). There were no significant differences in terms unplanned pregnancy, the use of family planning method, the number of pregnancy follow-ups and the frequency of Pap smears and mammography. There are no significant differences in terms of healthy children follow-ups, vaccination, vitamin D and iron supplementation (P>0.05). It was found that the duration of total breastfeeding increased after reorganization of primary care (P<0.001).
Keywords: child health care; Family Health Center; Health Transformation Program; preventive services; primary health care; reproductive health; COVERAGE